(untitled) (The Gaze: Journal of Tourism and Hospitality, 2021)
Tourism is one of the world’s largest and fastest growing industries. It acts as an engine for development through foreign exchange earnings and the creation of direct and indirect employment. Tourism plays a vital role to uplift the living status of people in specific areas worldwide. Tourism has potential for creating jobs and encourages income-generating activities and it also leads to infrastructure development. In Nepal, tourism has uplifted the socio-economical condition of the locals and given them ample opportunity to better their lives. It has created path towards the elimination of poverty and has significantly contributed to overall development of the nation. It is also one of the major sources of foreign exchange earning of the country. However, due to the impact of COVID-19, tourism has suffered unprecedented setback and its effect can be seen on global economy. It has rendered millions of people unemployed and huge investments have frozen and unable to generate business and move the economy. This study will analyze and study the challenges faced by tourism industry post COVID-19 in Nepal and try to provide answers for the recovery of tourism in Nepal. This study follows the qualitative methodology and the data is obtained through primary and secondary sources. As we move into the new era of travelling, tourism industry needs to adopt and focus on safety, personal hygiene and social distancing. Nepal is capable to adapt to the “new normal” and bounce back as it did post 2015 earthquake. But Nepal’s poor infrastructure, lack of implementation of rules and people’s laidback attitude could prove to be a hurdle and deter tourists and usher them to a more organized destination.